Interprofessional collaboration and communication in nursing homes: a qualitative exploration of problems in medical care for nursing home residents : study protocol - Müller, Christiane Annette; Weyerer, Siegfried (Journal of advanced nursing, 2015)
Aim: This study explores the current state of collaboration and communication between nurses and general practitioners in nursing homes, as well as needs and expectations of nursing home residents and their families. Finally, we aim to develop a new model of collaboration and communication. Background: Rising numbers of residents in nursing homes present a challenge for general practice and nursing in most Western countries. In Germany, general practitioners visit their patients in nursing homes, where nurses work in shifts. This leads to a big variety of contacts with regard to persons involved and ways of communication. Design: Qualitative multicentre study. Methods: Study part 1 explores needs and problems in interprofessional collaboration in interviews with nursing home residents and their relatives, general practitioners and nurses. Simultaneously, general practitioners' visits in nursing homes are observed directly. In study part 2, general practitioners and nurses will discuss findings from study part 1 in focus groups, aiming to develop strategies for the improvement of shortcomings in a participatory way. Based on the results, experts will contribute to the emerging model of collaboration and communication in a multi-professional workshop. Finally, this model will be tested in a small feasibility study. The German Federal Ministry of Education and Research approved funding in March 2011. Discussion: The study is expected to uncover deficits and opportunities in interprofessional collaboration in nursing homes. It provides deeper understanding of the concepts of all involved person groups and adds important clues for the interaction between professionals and older people in this setting.